Development of Group Counseling Service Guidelines for Increasing Student Religiosity in Drug Abuse Prevention - Dalimunthe, Hujaipah; Firman, Firman; Bentri, Alwen (Universitas Negeri Padang, 2021)
The problem of abusing Nakoba among Vocational High School students tends to increase, and the implementation of group guidance has not yet touched religious attachments (Religiosity) as its source. This study aims to formulate a group guidance service guide in increasing religiosity for drug abuse prevention uses Research and Development (R&D) with the ADDIE approach. The research subjects were students and school counselors in vocational high schools. Data were collected qualitatively and quantitatively. Quantitative data were collected through a religiosity questionnaire in drug abuse prevention. In comparison, qualitative data were collected through observation, interviews, and document analysis. Quantitative data were analyzed with statistics. Based on the study results, it was found that the guidance of group guidance services in increasing religiosity to prevent drug abuse was valid, practical, and useful.